Geopolitical Geworfenheit: Northern Europe After the Post-Cold War - Breitenbauch, Henrik (Journal of Regional Security, 2018)
The ‘greater Nordic space’ between Great Britain, Germany and Russia has over time varied with the balance of power. The Baltic States e.g. have been in and out of the space, rejoining by regaining sovereignty after the end of the Cold War. Russia’s actions in Ukraine and beyond during 2014 mark the end of the Post-Cold War period and its aspiration to peaceful integration. The small states of the greater Nordic space are now rediscovering their inescapable geopolitical nearness to Russia. Drawing on RSCT and Nordic-Baltic integration literature, the article contributes to understanding the Northern European part of the Euro-Russian Regional Security Complex. Theoretically, the article links RSCT and integration logics through the twin concepts of a ‘security region’ (given outside-in as one part of a negatively defined RSC), and a ‘political region’ (created inside-out under the shield provided by the security region). To link the two concepts, Heidegger’s idea of Geworfenheit, or thrownness, is employed to capture how the states of the greater Nordic space are always already subject to the dynamics underlying that space and how this condition affects the states’ interpretation of their changing surroundings, including translation into political regionality. Empirically, the article therefore argues that Russia’s new foreign policy has created a greater Nordic space ‘security region’ – supported by the United States – that is paving the way for new integration initiatives to a strengthened ‘political region’ inside the space, possibly as a ‘greater Nordic region’.